Penerapan Metode Lattice dalam Mengatasi Kesulitan Peserta Didik untuk Menyelesaikan Operasi Perkalian Bilangan Bulat di SMPN 6 Palu - muhlis muhlis; Ibnu Hadjar; Fajriani Fajriani; Baharuddin Paloloang (Universitas Tadulako, 2026)
This study aims to determine the level of students' ability in solving integer multiplication operations using the Lattice method at SMPN 6 Palu in grade VII. The type of research used in this study is descriptive research with a qualitative approach. The research data was collected through tests, observations, and interviews. The results of the study after using the Lattice method showed a difference in students' scores before and after using the Lattice method. Before using the lattice method, the average score of all students was only 62.3, but after using the lattice method, the average score of all students increased to 75.0. However, the increase was not significant, meaning not all students experienced it. It can be said that almost all students experienced difficulties in solving problems with varying error locations, such as students being less careful or considering the problem easy, students not understanding the concept of the problem, students not mastering multiplication operations or not memorizing multiplication, and finally, the lack of carefulness in students when working on problems.